What root of x does the expression (3^3/8)^2/3 yield?
square root
cube root
fourth root
eighth root

(3^3/8)^2/3 = 3^(3/8*2/3) = 3^(1/4)

s

Question

Asked 1/5/2015 4:56:05 PM

Updated 1/5/2015 7:18:53 PM

1 Answer/Comment

Rating

3

(3^3/8)^2/3

= 3^(3/8*2/3)

= 3^(1/4)

= 3^(3/8*2/3)

= 3^(1/4)

Added 1/5/2015 7:18:53 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/5/2015 10:32:32 PM]

Find the quotient.
n ^7 ÷ n ^3

Question

Not Answered

Updated 1/6/2015 3:51:36 AM

1 Answer/Comment

h^6 ÷ h = h^5

Added 1/6/2015 3:51:36 AM

This answer has been confirmed as correct and helpful.

Find the quotient.
4 ^r ÷ 4 ^s User: 11 ^3 ÷ 11 ^3 = 1,331
True
False **Weegy:** False **User:** Simplify.
y ^5 • y ^3 ÷ y ^2 **Weegy:** y^5 ? y^3 ? y^2; y^8 ? y^2 = y^6 **User:** Simplify.
y ^5 ÷ y ^3 • y ^2 **Weegy:** y^5 ? y^3 ? y^2; y^8 ? y^2 = y^6 **User:** Simplify.
n ^6 • n ^5 • n ^4 ÷ n ^3 • n ^2 ÷ n
**User:** Simplify.
n ^6 • n ^5 ÷ n ^4 • n ^3 ÷ n ^2 • n **User:** Simplify 3^a • 3^b ÷ 3^c ÷ 3^d.
The exponent on 3 is _____. **Weegy:** 8/9 Any other question? Please click "Good" if satisfied with the answer (More)

Question

Not Answered

Updated 1/18/2015 8:42:11 PM

5 Answers/Comments

4^r ÷ 4^s

= 4^(r - s)

= 4^(r - s)

Added 1/5/2015 5:45:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 4:20:59 AM]

y^5 ÷ y^3 • y^2

= y^2*y^2

= y^4

= y^2*y^2

= y^4

Added 1/5/2015 5:50:36 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 4:21:15 AM]

n^6 • n^5 • n^4 ÷ n^3 • n^2 ÷ n

= n^11 • n^4 ÷ n^3 • n^2 ÷ n

= n^15 ÷ n^3 • n^2 ÷ n

= n^12 • n^2 ÷ n

= n^14 ÷ n

= n^13

= n^11 • n^4 ÷ n^3 • n^2 ÷ n

= n^15 ÷ n^3 • n^2 ÷ n

= n^12 • n^2 ÷ n

= n^14 ÷ n

= n^13

Added 1/5/2015 5:52:03 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 4:21:32 AM]

n^6 • n^5 ÷ n^4 • n^3 ÷ n^2 • n

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

Added 1/5/2015 5:53:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 4:21:43 AM]

Simplify 3^a • 3^b ÷ 3^c ÷ 3^d. The exponent on 3 is a + b - c - d .

3^a • 3^b ÷ 3^c ÷ 3^d

= 3^(a + b) ÷ 3^c ÷ 3^d

= 3^(a + b - c ) ÷ 3^d

= 3^(a + b - c - d)

3^a • 3^b ÷ 3^c ÷ 3^d

= 3^(a + b) ÷ 3^c ÷ 3^d

= 3^(a + b - c ) ÷ 3^d

= 3^(a + b - c - d)

Added 1/18/2015 8:42:11 PM

Find the product.
(0.5n ^5)^2(10n ^7) ^3 **Weegy:** Is there a second part to this question? such as C= 0.25n
**User:** Find the product. .
-7(-a ^2)^2(-b ^3) **Weegy:** -7(-a^2)*2(-b^3) = (7a^2)(-2b^3) = -14a^2b^3 **User:** Find the product.
(y ^2)^5 · y ^8 **Weegy:** Here are some characteristics of grace and forgiveness: patience, kindness, mercy, unconditional love, empathy, and healing. All of these characteristics result in wholeness and inner peace. [
] (More)

Question

Not Answered

Updated 1/5/2015 9:52:12 PM

3 Answers/Comments

(0.5n^5)^2(10n^7) ^3

= 0.25n^10*1000n^21

= 250n^31

= 0.25n^10*1000n^21

= 250n^31

Added 1/5/2015 9:50:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 1:11:21 AM]

-7(-a^2)^2 (-b^3)

= -7*a^4 * (-b^3)

= 7a^4b^3

= -7*a^4 * (-b^3)

= 7a^4b^3

Added 1/5/2015 9:51:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 1:11:39 AM]

(y^2)^5 · y^8

= y^10*y^8

= y^18

= y^10*y^8

= y^18

Added 1/5/2015 9:52:12 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/6/2015 1:11:57 AM]

Find the product.
(3p ^4)^3 · (p ^2)^7 **Weegy:** The product of (3p^4)^3 * (p^2)^7 is =27p^26
Solution:
= 3^3 (p^4)^3 * (p^2)^7
= 27 p^12 * p^14
=27p^26
**User:** Find the product.
(-2x ^2)^3 ·3x (More)

Question

Not Answered

Updated 1/5/2015 9:56:11 PM

1 Answer/Comment

(-2x^2)^3 ·3x

= -8x^6*3x

= -8x^7

= -8x^6*3x

= -8x^7

Added 1/5/2015 9:56:11 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/6/2015 12:35:59 AM]

Find the product.
(fg)^9 **Weegy:** (fg)^9 = f^9g^9 **User:** Find the product.
(-7p)^3 **User:** Find the product.
(-7p)^3 **User:** Find the product.
(-4·3·2)^2 **User:** Find the product.
(10^2)^3 (More)

Question

Not Answered

Updated 1/5/2015 5:00:23 PM

2 Answers/Comments

(-4 * 3 * 2)^2

= (-24)^2;

= 576

= (-24)^2;

= 576

Added 1/5/2015 4:59:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/6/2015 5:55:42 AM]

31,073,294

questions answered

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

PranaMachine

$80.97

Hearts 1,653 Views 6,405 Streams 87

phpmicro

$37.30

Hearts 1,031 Views 71,231 Streams 91

jezziem

$22.30

Hearts 663 Views 20,525 Streams 29

emdjay23

$11.50

Hearts 375 Views 5,008 Streams 23

Arolf1988

$11.05

Hearts 283 Views 3,180 Streams 19

There are no comments.